PELUANG ARSIPARIS MENJADI PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID): Array - Sudiyanto Sudiyanto (Arsip Nasional Republik Indonesia, 2014)
Every Public Agency shall establish PPID as the implementation of Law Number 14 of 2008 on Public Information Transparency. This study is to determine whether PPID is relevant when it is assumed by Archivists. Analyses will be performed by synchronizing tasks with duties of PPID, Archivists and archival management elements. Based on the analyses, the tasks of PPID are very consistent, even some of them are same with the tasks of Archivists. PPID and Archivists together perform creation, management, security tasks and information services. Thus it is very relevant when PPID is performed by Archivists to serve information transparency within Public Agency.